β-cell Jagged1 is sufficient but not necessary for islet Notch activity and insulin secretory defects in obese mice - Nina Suda; Alberto Bartolomé; Jiani Liang; Jinsook Son; Yoko Yagishita; Christian Siebel; Domenico Accili; Hongxu Ding; Utpal B. Pajvani (Elsevier, 2024)
Objective: Notch signaling, re-activated in β cells from obese mice and causal to β cell dysfunction, is determined in part by transmembrane ligand availability in a neighboring cell. We hypothesized that β cell expression of Jagged1 determines the maladaptive Notch response and resultant insulin secretory defects in obese mice. Methods: We assessed expression of Notch pathway components in high-fat diet-fed (HFD) or leptin receptor-deficient (db/db) mice, and performed single-cell RNA sequencing (scRNA-Seq) in islets from patients with and without type 2 diabetes (T2D). We generated and performed glucose tolerance testing in inducible, β cell-specific Jagged1 gain-of- and loss-of-function mice. We also tested effects of monoclonal neutralizing antibodies to Jagged1 in glucose-stimulated insulin secretion (GSIS) assays in isolated islets. Results: Jag1 was the only Notch ligand that tracked with increased Notch activity in HFD-fed and db/db mice, as well as in metabolically-inflexible β cells enriched in patients with T2D. Neutralizing antibodies to block Jagged1 in islets isolated from HFD-fed and db/db mice potentiated GSIS ex vivo. To demonstrate if β cell Jagged1 is sufficient to cause glucose tolerance in vivo, we generated inducible β cell-specific Jag1 transgenic (β-Jag1TG) and loss-of-function (iβ-Jag1KO) mice. While forced Jagged1 impaired glucose intolerance due to reduced GSIS, loss of β cell Jagged1 did not protect against HFD-induced insulin secretory defects. Conclusions: Jagged1 is increased in islets from obese mice and in patients with T2D, and neutralizing Jagged1 antibodies lead to improved GSIS, suggesting that inhibition of Jagged1-Notch signaling may have therapeutic benefit. However, genetic loss-of-function experiments suggest that β cells are not a likely source of the Jagged1 signal.